2023
DOI: 10.1101/2023.02.10.528073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Helminth infection impacts hematopoiesis

Abstract: Helminth infections are common in animals. However, the impact of a helminth infection on the function of hematopoietic stem cells (HSCs) and other hematopoietic cells has not been comprehensively defined. Here we describe the hematopoietic response to infection of mice with Schistosoma mansoni, a parasitic flatworm which causes schistosomiasis. We analyzed the frequency or number of hematopoietic cell types in the bone marrow, spleen, liver, thymus, and blood, and observed multiple hematopoietic changes cause… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…However, it has been suggested that these infections decrease erythropoiesis by releasing nitric oxide. Nitric oxide can reduce the deformability of erythrocytes, leading to increased red blood cell destruction (Wijshake et al, 2023). Helminthic infestations during pregnancy can have several detrimental effects on both maternal and foetal health (Mpairwe et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been suggested that these infections decrease erythropoiesis by releasing nitric oxide. Nitric oxide can reduce the deformability of erythrocytes, leading to increased red blood cell destruction (Wijshake et al, 2023). Helminthic infestations during pregnancy can have several detrimental effects on both maternal and foetal health (Mpairwe et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, helminth infestations, particularly hookworm infestations, have been identified as significant contributors to severe anaemia during pregnancy in Sub-Saharan Africa (Brooker et al, 2007). Studies have shown that helminthic infestations during pregnancy, such as hookworm infestations, can cause occult or overt intestinal blood loss due to mucosal or submucosal invasion, further exacerbating anaemia (Mpairwe et al, 2014;Wijshake et al, 2023). Foetal complications such as foetal growth restriction and low birth weight can also arise (Brooker et al, 2007;Mpairwe et al, 2014).…”
Section: Discussionmentioning
confidence: 99%